Preparation of MOF/polypyrrole and flower-like MnO2 electrodes by electrodeposition: High-performance materials for hybrid capacitive deionization defluorination. (1st February 2023) - Kang, Hu; Zhang, Dan; Chen, Xiuping; Zhao, Haosen; Yang, Dongdong; Li, Yiming; Bao, Mutai; Wang, Zhining
Highlights: MOF/polypyrrole and MnO2 Electrodes were prepared by electrochemical method. The two electrodes were combined as a hybrid capacitive deionization (HCDI) system. The HCDI system has high selectivity for fluoride. Fluoride removal capacity at 1.2 V reached 55.12 mg/g. Elucidated fluoride removal mechanism. Abstract: Fluorine pollution has become a global public health problem due to its adverse health effects. Adsorption is the primary method for removing fluoride from drinking water. However, the adsorption method has disadvantages such as difficulty in recovering the adsorbent, and the need to add additional chemicals for regeneration, thereby causing secondary pollution, which limits further industrial applications. Capacitive deionization (CDI), as an emerging water treatment technology, has attracted widespread attention due to its advantages of simple operation, low energy consumption and less environmental impact. In this study, a polypyrrole (PPy) film was prepared on a graphite substrate by electrodeposition, and then metal-organic framework Ce/Zn-BDC-NH2 (CZBN) was deposited on the PPy film by electrophoretic deposition to obtain CZBN/PPy electrode was obtained. The CZBN/PPy anode was then coupled with the MnO2 cathode for capacitive removal of fluoride in a CDI cell. Both CZBN/PPy and MnO2 electrodes exhibit pseudocapacitive behavior, which can selectively and reversibly intercalate F − (CZBN/PPy) and Na + (MnO2 ) ions. As expected, the CZBN/PPy-MnO2 system exhibits excellent fluorine removal performance. In 1.2 V, 100 mg/L F − solution, the F − removal capacity can reach 55.12 mg/g. It has high F − selectivity in the presence of some common anions, and can maintain high F − removal ability even after five adsorption regeneration processes. The mechanism of F − removal was studied by Fourier transform infrared spectroscopy (FTIR) and X-ray photoelectron spectroscopy (XPS). F − was mainly removed by electrostatic interaction and ion exchange with hydroxyl. The excellent defluorination performance of the CZBN/PPy-MnO2 system makes it have good practical application prospects. Graphical abstract: Image, graphical abstract